PHYSICAL DEVELOPMENT AND SPECIFIC WORKABILITY OF PROFESSIONAL BASKETBALL TEAM OVER LARGE PERIOD OF TIME - Yanar, Şenol (Acta Scientiae et Intellectus, 2024)
The purpose of the present study is to optimize the training process of professional basketball players. The optimization to be done based on the physical development and the specific workability. Object of study are the indicators of physical development, specific physical, technical and tactical indicators of sport performance. The participants of the present study are 18 professional male basketball players playing as cadets in a Turkish professional basketball club. We have applied a complex test battery which examines general and specific physical skills. The test battery consists of 7 tests for specific physical workability and 5 tests for technical and tactical skills. The assessment data is compared with previously not published results from the estimation of the specific workability and on the same team with some changes in terms of players since then. The previous assessment has been conducted 2 years prior to the present study. In conclusion, we found that the selection of the team members has been done properly considering the requirements of the game. Although professional athletes, some of the participants of the study could be considered as overweight according to the standards. This requires some modulations on the dietary of the players. The values of most of the indicators of the physical workability and the specific technical and tactical skills remain without a significant change in comparison with the results estimated 2 years ago. The results of the study show that most of the examined sport specific skills remain relatively steady which should be positively valued because the training staff manages to maintain the level of sport performance for the last two years.